PENGARUH KONSENTRASI KENTOS KELAPA TERHADAP DEGRADASI LEMAK DAGING AYAM: (The Effect of Coconut Embrio (Kentos) Concentration on Chicken Fat Degradation) - Laras Budyghifari; Sitti Syuhada Dwi Arista; Andi Nur Fajri Suloi; Amran Laga (Hasanuddin University Food Science and Technology Study Program, 2019)
Cardiovascular diseases such as hypertension, coronary heart disease, heart failure, and stroke cause 17.9 million people die or 31% of all global deaths (World Health Organization, 2017). This disease is generally caused by high consumption of sources of fat. Thigh chicken meat is one of the highest food that contain fat (7%) compared to beef cuts (6.8%) and lamb meat (4.9-5.2%) with high consumption levels (Dinh et al., 2011). The crude lipase enzyme extract can efficiently hydrolyze fat into free fatty acids and glycerol. This study was conducted to look the effect of the concentration of coconut kentos as a source of lipase enzymes on fat hydrolysis of thigh chicken meat. Coconut kentos is prepared and then applied to chicken meat with a concentration of 1-5% and 10-50%. Parameters of observation include changes in pH, total dissolved solids, and free fatty acids. The best results for each parameter were concentration 10% with free fatty acids2.99%, total dissolved solids 4.1%, and pH of 5.3